Beam Shaping for Advanced Laser Materials Processing. Issue 2 (April 2015) - Fuse, Keiji
Abstract For recent industrial materials processing with advanced high power lasers, beam shaping optics are utilized as a key technology. Aspheric or diffractive beam shapers transform a Gaussian intensity profile of a single mode (TEM00) laser beam into a flattop one. While an aspheric beam shaper can make a circular flattop, a diffractive one can realize much flexibility in output beam shapes, like square, rectangular, linear, or other complex beam shapes. The beam shaping is often combined with a scanning optical system, consisting of galvanometric mirrors and an f‐theta lens. Those beam shapers are used for either pulsed or CW single mode laser applications, i. e. ablation, cutting, drilling, scribing, annealing, etc. of thin films or bulk materials. This article describes principles, design concepts and specification examples of those optical systems used in practical applications.